Respon Krisis PT Garuda Indonesia Pada Kasus Postingan Menu Rius Verandes - Intan Leliana; Susilowati Susilowati; Dhefine Armelsa; Chepy Nurdiansyah; Asriyani Sagiyanto (Universitas Bina Sarana Informatika, 2020)
Crisis is negative phenomenon that can occur in any company or organization, anytime and anywhere. The crisis has the potential to be highlighted by the mass media On the other hand, mass media can shape public perceptions according to their wishes. Therefore, companies must understand how the media works. A company's reputation depends on the speed of its response. The purpose of this study is to develop an in-depth description of the crisis response undertaken by Garuda Indonesia in response to Youtuber's post, Rius FernandesThis research method uses descriptive qualitative method with news content analysis method in several online media. The crisis response strategy provided by the Situational Crisis Communication Theory (SCCT) as a theoretical basis explains that in the Garuda Indonesia crisis response category in dealing with this problem, public communication management can be said to be inappropriate. The inability to manage a crisis that is quite small in scale (an imperfect product) caused the airline to suffer a multiplier loss due to a series of crises after which YouTuber posted